Distribution of Currents in 2 × 25 kV Electric Railway Systems under Normal Conditions - Elmer Sorrentino; Naren Gupta; Miguel Montilla-DJesus; Pablo Arriaga (International Transactions on Electrical Energy Systems)
This article shows a detailed analysis of the distribution of currents in 2 × 25 kV electric railway systems under normal conditions. The network equations are clearly formulated in a way that enables the presentation of a novel simplified analytical solution as well as the traditional numerical solution of the equation set. The simplified analytical solution is obtained when the transformer impedances are neglected, and under these conditions: (a) the distributions of currents are analytically deduced for cases with only one train; (b) the distribution of currents among autotransformers and between catenary and feeder can be easily understood, as well as the effect of the train position on the distribution of currents; and (c) the superposition method is applied for cases with multiple trains in order to clearly explain the distribution of currents from the results with only one train. On the other hand, the network equations are also numerically solved, including autotransformer impedances, and it is shown that their effect is very low, especially because these impedances are typically small. Therefore, the proposed analytical method is a good tool to obtain an easy and approximate solution for the distribution of currents in these systems, as well as an excellent tool to facilitate the understanding of that distribution.